2022
DOI: 10.1111/1745-9133.12575
|View full text |Cite
|
Sign up to set email alerts
|

Pretrial risk assessment instruments in practice: The role of judicial discretion in pretrial reform

Abstract: We explored the extent to which the implementation of a pretrial risk assessment instrument (PRAI) corresponded to changes in the pretrial processing of defendants using multiple administrative data sources from a large county in the southeastern United States. Our findings revealed little evidence of reductions in detention lengths or increases in the use of nonfinancial forms of release following the tool's adoption. This was largely attributable to the exercise of judicial discretion, as judges frequently d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Through pretrial reform efforts, many jurisdictions implemented pretrial risk assessments as an alternative to financial bail. Prior research has shown that implementation of pretrial risk assessments is associated with a reduction in financial bond decisions (Cooprider, 2009; Copp et al, 2022; Lowder et al, 2021; Sloan et al, 2018; Stevenson, 2018). This is true even in a state such as Indiana, where pretrial defendants retain a constitutional right to bail (Indiana Constitution, Article 1, §17).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Through pretrial reform efforts, many jurisdictions implemented pretrial risk assessments as an alternative to financial bail. Prior research has shown that implementation of pretrial risk assessments is associated with a reduction in financial bond decisions (Cooprider, 2009; Copp et al, 2022; Lowder et al, 2021; Sloan et al, 2018; Stevenson, 2018). This is true even in a state such as Indiana, where pretrial defendants retain a constitutional right to bail (Indiana Constitution, Article 1, §17).…”
Section: Discussionmentioning
confidence: 99%
“…However, among typically sized matrices (i.e., those that were 3 × 3 or 3 × 4), we found no consistent evidence that pretrial risk assessment consideration was lower among more serious charge types. Finally, previous studies have examined rates of adherence to structured guidelines in the pretrial context (Copp et al, 2022; Danner et al, 2015; Lowder et al, 2021; Lowder & Foudray, 2021), and we used these estimates to project the potential influence of risk assessments on decisions. We do not know the exact rates of adherence to structured guidelines across all 29 counties that provided matrices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations